Konstruksi Keilmuan Islam (Studi Pemikiran Ibnu Rusyd tentang Ontologi dan Epistimologi) - Salabi, Agus Salim (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2021)
This study aims to deeply construct Islamic scholarship from the point of view of the great Islamic scholar Ibn Rushdi. This research is a qualitative type of literature method. Data collection techniques were taken from relevant reference sources from research sources and primary books. The results of the research show that broadly speaking, ontology and epistemology are related to two main questions (a) what can be known? (what can be known?) and b) how can it be known? (how can it be known?). The first question relates to the source of knowledge, the second question relates to how to acquire knowledge. Based on this, ontology and epistemology are related to two main studies, namely where knowledge comes from, and how knowledge should be extracted. According to Ibn Rushd, human knowledge is obtained through three potentials, namely the power of the senses (al-quwwah al-ḥasāsah), the power of imagination (al-quwwah al-mutakhayyilah), and the power of thought (al-quwwah an-nāṭiqah). To get general conclusions from the observations on particular objects above, there are three stages mentioned by Ibn Rushd, namely: 1) abstraction, 2) combination, 3) assessment.